Perlindungan Hukum terhadap Pengetahuan Tradisional Marosok Sebagai Budaya Masyarakat di Sumatera Barat - Rizkita Kurnia Sari (Media Nusantara, 2021)
Traditional Knowledge is part of Intellectual Property Rights. Marosok is one of the cultures of the Minangkabau people in West Sumatra. Its categorized as traditional knowledge because the tradition comes from ideas or inventions which then become habits and caried out from generation to generation. Habits becomes a culture in the community. Legal protection is given to Marosok as an acknowledgment that Marosok cultureis a tradition of the Minangkabau people. In addition, to avoid any recognition from other parties outside the indigenous peoples where the culture originates. To find out more about how legal protection is given to Marosok and as one of the traditional knowledge in West Sumatra and how the Indonesian Government prevents the claim of intellectual property rights for Indonesian culture, especially Marosok by other countries, the author conducted a study on Legal Protection against Marosok traditional knowledge as Minangkabau community culture in West Sumatra. This study uses a qualitative method analytical descriptive nature prioritizing research on secondary data supported by the result of the field research. Data Analysis based on research, it can be seen that legal protection is needed for Marosok as traditional knowledge of the Minangkabau people of West Sumatra. The method of data collection is through library research and field studies.